Studies on Homalomeneae (Araceae) of Borneo II: The Homalomena of Nanga Sumpa (Batang Ai) – Novel and Pre-existing Taxa, and Notes on Iban Usages - Boyce, P.C; Wong, S Y; Fasihuddin Badruddin, Ahmad (Singapore Botanic Garden, 2010)
Fieldwork targeting indigenous Homalomena at Nanga Sumpa. part of the Batang Ai drainage system (Sri Aman Divison. Sarawak) revealed 14 species of which six are novel and herewith described: Homalomena atrox P.C.Boyce. S.Y.Wong & Fasihuddin. H. clandestine! P.C.Boyce. S.Y.Wong & Fasihuddin. H. hanneae P.C.Boyce. S.Y.Wong & Fasihuddin, H. sengkenyang P.C.Boyce. S.Y.Wong & Fasihuddin. H. symplocarpiifolia P.C.Boyce. S.Y.Wong & Fasihuddin. and H. vivens P.C.Boyce. S.Y.Wong & Fasihuddin. Of the six Homalomena species present at Batang Ai for which there are pre-existing names, two. H. borneensis Ridl. & H. humilis (Jack) Hook.f.. are species complexes still awaiting a full taxonomic and systematic investigation, and are treated here as morpho-taxa to which we apply the earliest applicable epithet. The remaining four species with available names have only recently been described: H. geniculata M.Hotta (1967): H. vagans P.C.Boyce (1994). and H.josefii P.C.Boyce & S.Y.Wong, and H. pseudogeniculata P.C.Boyce & S.Y.Wong (2008). Additionally, two further species located during fieldwork. that while unarguably novel based on their vegetative morphology, were not located as fertile plants and have yet to flower in cultivation: they are here treated as sp. nov. A & B. Of the 14 species present at Batang Ai. five have significance in the ethnobotany of the indigenous Iban people of the Ai drainage, and of these five, four are novel. A key to the Homalomena in the Batang Ai drainage area is given, and all species are illustrated.